DAYASAING INDUSTRI KECIL SEDERHANA (IKS) MAKANAN HALAL DALAM MENGHADAPI AFTA - Dan, Abd. Razak; Shahadan, Faridah; Mohd Noor, Mohd Ali; wiyadi, wiyadi (Benefit: Jurnal Manajemen dan Bisnis, 2006)
Globalization and liberalization form a new dimension in trading. To facing emulation in theglobal stage, each state in the world tries to improve its competitiveness especially in manufacturing andservices sector. The lawful food industries are not quit of this phenomenon. Looking into the mostmanufacturing lawful food industries in Malaysia consist of small and medium industries, this paperaim to analyse Malaysia lawful food of small and medium industrial competitiveness in face of AFTAwith focusing to financial, technological and human resource aspect.